Solubility and Dissolution Enhancement of Domperidone using 2-hydroxypropyl-β-cyclodextrin by Kneading Method (Asian Journal of Pharmaceutics (AJP), 2017)
Objective: The objective of this study was solubility and dissolution enhancement of domperidone (DOM), and further they were formulated as mouth dissolving tablets (MDT). Method: DOM-solid dispersion (DOM-SD) was prepared using suitable complexing agent (2-hydroxypropy-β-cyclodextrin) by kneading method; the solid dispersion prepared was further formulated into MDT by direct compression using super disintegrants (Kyron-T314, sodium starch glycolate, and Plantago ovata husk) in varying ratios. The prepared SDs were evaluated on Fourier transform infrared (FT-IR), percent yield, percent drug content (DC), saturation solubility, phase solubility, in vitro release, pre- and post-compression test. Results and Discussions: Percent yield and DC of DOM-SD was 81.48 ± 4.35% to 95.31 ± 3.01% and 91.96 ± 0.72% and 99.28 ± 0.23%, respectively, saturation solubility was at higher in DOM-SD as compared to DOM alone, FT-IR studies revealed no drug excipient interaction except DOM-2-hydroxypropyl-β-cyclodextrin (2- HPβCD) which was deliberate, formulation KF5 showed best in vitro dissolution for DOM-SD. Pre-compression parameters like supported formulation of MDT of DOM. Post-compression parameters such as thickness, hardness, weight variation, friability, percent DC, water absorption ratio, wetting time, disintegration time, and in vitro dissolution suggested effective improvement and prompt release in the simulated conditions. The selected formulation KF2 also showed good stability data at accelerated conditions. Conclusion: DOM-SD was prepared using 2HPβCD which effectively enhanced DOM solubility and dissolution; moreover an effective DOM-MD was also prepared for prompt relief from nausea and vomiting.